2015
DOI: 10.7554/elife.09419
|View full text |Cite
|
Sign up to set email alerts
|

The chemokine CXCL13 in lung cancers associated with environmental polycyclic aromatic hydrocarbons pollution

Abstract: More than 90% of lung cancers are caused by cigarette smoke and air pollution, with polycyclic aromatic hydrocarbons (PAHs) as key carcinogens. In Xuanwei City of Yunnan Province, the lung cancer incidence is among the highest in China, attributed to smoky coal combustion-generated PAH pollution. Here, we screened for abnormal inflammatory factors in non-small cell lung cancers (NSCLCs) from Xuanwei and control regions (CR) where smoky coal was not used, and found that a chemokine CXCL13 was overexpressed in 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 69 publications
2
75
0
Order By: Relevance
“…16,17 Importantly, the B cell chemoattractant CXCL13, secreted by tumor cells, follicular dendritic cells, and T follicular helper cells in human lung tumor lesions, was shown to be responsible for the influx of B cells into the tumor. 16,18,19 Upon entering the local microenvironment, tumor antigens released from lung cancer cells aid in B cell aggregation and trigger B cellmediated antigen presentation, which facilitate the maintenance of B cell activation and proliferation. 19,20 Immunohistochemistry (IHC) and flow cytometric analysis show that all major subsets of B cells can be found within TIB populations (Table 1).…”
Section: The Infiltration Location and Maintenance Of Tibs In Humanmentioning
confidence: 99%
“…16,17 Importantly, the B cell chemoattractant CXCL13, secreted by tumor cells, follicular dendritic cells, and T follicular helper cells in human lung tumor lesions, was shown to be responsible for the influx of B cells into the tumor. 16,18,19 Upon entering the local microenvironment, tumor antigens released from lung cancer cells aid in B cell aggregation and trigger B cellmediated antigen presentation, which facilitate the maintenance of B cell activation and proliferation. 19,20 Immunohistochemistry (IHC) and flow cytometric analysis show that all major subsets of B cells can be found within TIB populations (Table 1).…”
Section: The Infiltration Location and Maintenance Of Tibs In Humanmentioning
confidence: 99%
“…In keeping with the previously reported role for CXCR5 + DCs in promoting the T helper 2 response development following Hp infection (Leó n et al, 2012), we found that the increase in CXCL13expressing cells located at the IFR correlated with increased accumulation of DCs in close association with ER-TR7 + fibers ( Figure S2E). The IFR is also known to be the site where antigen-activated B cells position themselves to receive T cell help (Garside et al, 1998;Wang et al, 2015). Thus, CXCL13 production by interfollicular MRC-like cells is likely to play an important role in the T cell-DC interactions that are known to be important in driving T helper 2 responses.…”
Section: (Legend Continued On Next Page)mentioning
confidence: 99%
“…Tobacco-specific nitrosamines, 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) and N’-nitrosonornicotine (NNN) are reported to cause lung cancer and oral cavity cancer [ 3 ]. PAHs are associated with several cancers such as skin, lung, oral, and breast cancer [ 4 7 ]. Among the hundreds of PAHs present in the cigarette smoke, benzo(a)pyrene (BaP) is the most extensively studied PAH due to its known carcinogenic effects.…”
Section: Introductionmentioning
confidence: 99%